Optimizing public seating design in post-pandemic urban community parks: a comprehensive framework - Zhang, Ling; Perumal, Velu; Abdul Rahman, Ahmad Rizal; Yahaya, Mohd Faiz; Tualeka, Abdul Rohim (Horizon Research Publishing, 2024)
In the post-pandemic context, public seating furniture, an essential part of urban community parks, is vital in meeting people's needs for a comfortable resting space. The current design and layout of public seating in community parks in the post-pandemic period do not meet the needs of different groups of people in many aspects. This study aims to develop a comprehensive design framework that covers the user characteristics, use patterns, space features, location, and activity characteristics of public seating in community parks. This framework will provide valuable reference information for industrial designers and urban planners to optimise the layout and design of park seating to further meet the needs and expectations for improved public seating in the post-pandemic period. This research used an on-site observation method and statistical analysis of data using Excel. Research shows that users of community park seating furniture cover all age groups, including special groups (pregnant women and people with disabilities). Although individual use is predominant, users have expectations of social interaction. Preferred seating locations are close to children's play areas, beautifully landscaped, and shaded tree areas. The type of activity is statistically diverse and includes accompanying children, socialising, watching dynamic activities, and using mobile phones. Based on the findings, however, there are limitations to this study, such as the limited sample size and the choice of observation periods and locations. In conclusion, the design framework is valuable to improve the attractiveness and promote the sustainable development of urban community parks.